CRISPR/Cas9 ribonucleoprotein mediated DNA-free genome editing in larch - Miaomiao Ma; Chan Zhang; Lijing Yu; Jingli Yang; Chenghao Li (Forestry Research)
Here, a DNA-free genetic editing approach is presented for larch by delivering ribonucleoprotein complexes (RNPs) of CRISPR/Cas9 through particle bombardment. The detailed procedure encompasses creating a transgenic system via particle bombardment for the transformation of embryogenic callus, validating the functionality of RNPs, optimizing coating and delivery techniques, enhancing somatic embryo maturation, regenerating plantlets, and precisely identifying mutants. The optimal particle bombardment parameters were determined at 1,100 psi and a distance of 9 cm and the editing efficiency of the targets was verified in vitro. Subsequently, the RNPs were transferred into the embryogenic callus. Mutant plants were obtained in targets 1 and target 2. The efficiencies of obtaining albino somatic embryos were 1.423% and 2.136%, respectively. A DNA-free particle bombardment transformation method suitable for larch has been established. The present study demonstrates that the DNA-free editing technology has been successfully implemented in larch. This method can achieve targeted genome editing in the larch genome, avoiding the risks of genomic integration and the lengthy breeding cycles associated with traditional transgenic methods. Moreover, it may be widely applicable for producing genome-edited conifer plants and holds great promise for commercialization.